Pelatihan Pembuatan Simple Drying Building Bagi Mama-Mama Asli Papua Dusun Sarsang - Simorangkir, Yosi Valentina; Nurhuzna, Atiza (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2023)
In Sarsang Hamlet, most of the residents are native Papuans where they like to plant tubers and bananas as food ingredients for rice substitutes, but they have also started processing tubers and bananas into processed products in the form of chips. The purpose of this service is to provide training to Papuan women from Dusun Sarsang regarding how to process banana products besides making chips but in the form of other processed products, namely sale bananas using the Simple Drying Building.The methods used are Experimental and Applicative, counseling and training on making Simple Drying Buildings using simple and inexpensive materials. The mechanism is carried out in 4 stages, namely (1) designing a Simple Drying Building (Unmus Architecture Laboratory), (2) Building/making a Simple Drying Building (Unmus Architecture Laboratory), (3) Preparation of Materials and Tools for Extension and Training (Unmus Architecture Laboratory), (4) Counseling on making Pisang Saleh and how to use the Drying Building.The results of this service are expected to use Simple Drying Buiding to make the process of making sale bananas and other products (with the drying process) healthier (hygienic free from dust, flies and other bacteria), besides that the native Papuan mothers of Sarsangg village can make or produce new business (opaque, salted fish and others) independently so as to improve the economy of indigenous Papuan women.